SHORTAGE OF TYPOLOGICALLY INFORMED TEACHING MATERIALS AND REFERENCE GRAMMARS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The present article examines the typology of the verb as a central part of speech in English and Uzbek from both theoretical and applied perspectives. By drawing on cross-linguistic typology, reference grammars, and applied linguistics literature, it explores how verbal categories such as tense, aspect, mood, and voice are realized differently in the analytic structure of English and the agglutinative morphology of Uzbek. The study further considers pedagogical implications, highlighting the need for typologically informed teaching materials to address learner difficulties arising from structural contrasts.